Disruptive Healthcare Provider Behavior An Evidence-Based Guide - Vukmir, Rade B. (Springer International Publishing : Imprint: Springer, 2016)
This book explores a rapidly growing area of discussion in the health care industry, disruptive behavior in medical providers. The presence of disruptive behavior adversely impacts the providers of all disciplines: paraprofessional personnel, nurses, physicians and administrators. But more importantly, there may be a greater detrimental effect on quality and patient safety. This has led to mandated regulatory requirements that assist healthcare institutions in developing programs to address the problem. The book presents an evidence-based analysis of the disruptive provider behavior that defines the incidence, demographics, and profile of the behavior; discusses the specialties and work locations predisposed, as well as the interface with residents and nurses. The importance of patient safety, economic, and legal issues are addressed by a comprehensive, management strategy to effect positive, sustainable culture change in healthcare.